ANALYSIS OF INEQUALITY IN ECONOMIC DEVELOPMENT BETWEEN DISTRICT IN SOPPENG REGENCY 2008-2018 - Amriadi, Amriadi; Umar, Andi (Jurnal Ekonomi Balance, 2020)
This study aims: 1) Knowing the development and level of progress of economic development in each district in the period 2008-2018. 2) Knowing the effect of population and high school and tertiary education levels on the level of economic development inequality. 3) Knowing the effect of the number of poor families on the level of inequality in economic development. 4) Knowing the effect of population growth on the level of inequality in economic development. This research is a quantitative research. The data used in this research are secondary data from 8 sub-districts in Soppeng Regency in 2008-2018. The analysis technique used is quantitative analysis using panel data regression analysis model Fixed Effect. The results of this study indicate that: 1) The analysis using panel data regression shows that the regional share growth component variable is not included or removed from the model. 2) The population variable with high school and tertiary education levels has a significant and positive effect on inequality in economic development. 3) The variable number of poor families has a significant and negative effect on inequality in economic development. 4) The population growth variable does not have a significant effect on inequality in economic development.